Tinjauan Yuridis Terhadap Jual Beli Atas Tanah Yang Termasuk Harta Perkawinan (Gono-Gini) Yang Dijual Istri Tanpa Persetujuan Suami (Studi Putusan Mahkamah Agung Nomor 3325/K/Pdt/2020) - Elsa Aprilia Rambe; hasim purba; sutiarnoto (Jurnal Hukum Lex Generalis, 2025)
In marriage, marital property (gono-gini) arising from valid marital bonds requires spousal consent for transfer. This study employs normative juridical methodology with descriptive analytical approach to examine Temporary Land Deed Officials' (PPATS) responsibility in facilitating marital property sales without spousal consent based on Supreme Court Decision Number 3325K/PDT/2020. Research findings demonstrate that PPATS bears administrative and disciplinary accountability, sales agreements are void under Article 1320 Indonesian Civil Code, good-faith buyers retain legal protection, and parties may file deed annulment suits or pursue mediation to ensure legal certainty and justice.